The Effect of EDTA Functionalization on Fe3O4 Thermal Behavior - Fumis, Daniel B. [UNESP]; Silveira, Maria L.D.C. [UNESP]; Gaglieri, Caroline [UNESP]; Ferreira, Laura T. [UNESP]; Marques, Rodrigo F.C. [UNESP]; Magdalena, Aroldo G. [UNESP] (FapUNIFESP (SciELO), 2022)
The surface of Fe3O4 nanoparticles is very reactive and can oxidize to γ-Fe2O3 (maghemite) and α-Fe2O3 (hematite) structures. Based on this, the oxidation process of Fe3O4 nanoparticles must be prevented, and one of the strategies is surface functionalization with organic or inorganic molecules. Thus, this study analyzed the thermal behavior of Fe3O4 and Fe3O4-EDTA nanoparticles using X-ray diffraction (XRD), simultaneous thermogravimetry-differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC). Results showed that γ- Fe2O3 was obtained as an intermediate in Fe3O4 and Fe3O4-EDTA decomposition, as confirmed by TG-DTA and DSC curves. Moreover, Fe3O4-EDTA exhibited a temperature peak (Tp = 573.5°C) of phase transformation (γ-Fe2O3 → α-Fe2O3) higher than that of Fe3O4 (Tp = 533.0°C), confirming that EDTA molecules stabilized the nanoparticles efficiently. The kinetic behavior of samples changed, and the activation energy for functionalized samples decreased.
Keywords: Hematite; Maghemite; Magnetite; Non-isothermal kinetics